REVITALISASI PENGEMBANGAN SEKTOR PENDIDIKAN DI KOTA PEKANBARU - Siska "; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Revitalization is an effort of increasing the economic value of land through rebuilding a building to improve the quality of the previous one. By the increasing of school-age population number in the Pekanbaru every year, it is necessary to increase the availability of school facilities and infrastructures in the form of buildings and furniture, as regulated in the Regulation of the Minister of National Education Number 24 of 2007 which says that the Standards for Facilities and Infrastructure in the form of Education units, land, buildings and availability of facilities and infrastructure. School development plans need to provide direction and guidance to school actors to change or strive for better schools standard. The theory used is the Danisworo theory that includes 3 stages which are revitalization: Physical Intervention, Economic Rehabilitation, and Social Revitalization. Qualitative approach is used in this study. The sources of data in this study are informants and documents. Data collection techniques are carried out by documentation and interviews while the data analysis technique is done by qualitative descriptive analysis. The results of this study indicate that the revitalization of the development of the education sector in Pekanbaru is said to be quite good in accordance with the decision of the mayor of Pekanbaru regarding to the determination of schools that receive the Special Allocation Fund. And also the revitalization of the development of the education sector is influenced by budget, communication and the system of work. Keywords: Revitalization, School, facilities and infrastructure